Purification and characterization of a new PLA2 of whole venom of Micrurus spixii - Valeriano-Zapana y Cols., J.A (2019)
A new PLA2, with myotoxic activity, was purified from de venom of Micrurus spixii, with a high degree of purity and molecular homogeneity by two chromatographic steps: molecular exclusion chromatography G-75 (1 cm x 60 cm) and high performance liquid chromatography pressure reverse phase (RP-HPLC). The SDS-PAGE electrophoresis shows a molecular mass ~ 14 kDa, which was confirmed by mass spectrometry MALDI-TOF with a molecular mass of 14149,005 Da. This new PLA2 showed a potent myotoxic local effect (intramuscular way) and systemic too (tail vein) in mice, at a concentration of 20ug/ml compared to other snake of the same gender and high inflammatory activity at a concentration of 5ug / ml. The reproducibility of biological activity through the pharmacological effects is only possible with the use of chemically homogeneous fractions that keep the integrity of the biology activity.